SMEs' Access to Finance in the Euro Area : What Helps or Hampers? - Ozturk, Bahar; Mrkaic, Mico. (Washington, D.C. : International Monetary Fund, 2014)
The monetary transmission mechanism in the euro area has been adversely affected by the recent crises. Using survey data on thousands of euro area firms, we study factors that affect the access to finance of SMEs. We find that changes in bank funding costs and borrower leverage matter for firms' access to finance. Increases in bank funding costs and borrowers' debt-to-asset ratios are significantly and negatively associated with firms' access to finance. The use of subsidies significantly improve access to finance of SMEs. Finally, access to finance is found to be positively related to firm size and firm age.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet